Sang Naga Membelit Asean: Kebijakan Ekonomi China Pasca Diterima sebagai Anggota WTO - Mursitama, Tirta Nugraha; Erwin, Haura Emilia (UI Scholars Hub, 2011)
Since its accession to the World Trade Organization (WTO), China has been playing its greater role as a new giant economy more actively in international trade and has succeeded in strengthening its economic relations with its neighboring countries including Southeast Asian countries, which are the members of ASEAN. This paper particularly discusses China's economic policies in ASEAN after China gained its membership in the WTO. We focuses mainly on the agreement on trade in goods under the scheme of ASEAN China Free Trade Area (ACFTA) and the investment agreement between China and ASEAN that affects its economic relations with ASEAN. We argue that China's economic policies in ASEAN as concrete and systematic implementation of